Kinetic and thermodynamic insights into sewage sludge torrefaction: Energetic optimization and safety considerations - Blanca Castells; Roberto Paredes; David León; Isabel Amez (Energy Nexus)
In the current energetic scenario, biofuels play a crucial role, with torrefaction being one of the most popular pretreatments as it significantly reduces the main disadvantages of these fuels. This study provides novel insights into torrefied sewage sludge as a solid biofuel by examining both the energetic conversion process and associated safety issues. To do so, torrefaction was carried out at three different temperatures (220 °C, 250 °C, and 300 °C) and two residence times (30 and 60 min), resulting in seven distinct samples. These samples underwent proximate analysis, thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) in air, nitrogen, and oxygen atmospheres to simulate combustion, pyrolysis, and determine heating values respectively. The analysis reveals that torrefaction at 300 °C for 60 min produces the best results, enhancing the higher heating value (HHV) by 6% and increasing reaction heat by 16%. Additionally, we observed lower pyrolysis activation energies in samples torrefied for 30 min compared to 60 min. The kinetic parameters were meticulously evaluated, showing a clear relationship between torrefaction parameters and pyrolysis activation energy. For instance, the activation energy (Ea) for raw sewage sludge was found to be between 338.02 kJ/mol and 375.43 kJ/mol. In contrast, torrefied samples showed reduced Ea values mostly under 300 kJ/mol. For the first time, we assessed self-ignition risk through TGA, finding that while most samples exhibit low risk, the increased heating value from torrefaction does elevate this risk. This comprehensive evaluation not only advances the understanding of sewage sludge torrefaction but also offers a practical framework for integrating biofuels into sustainable energy systems, supporting global efforts toward cleaner energy transitions.